Distribution of 5HT2A receptors in the human brain: comparison of data in vivo and post mortem - Forutan, F.; Estalji, S.; Beu, M.; Nikolaus, S.; Hamacher, K.; Coenen, H. H.; Vosberg, H.; Müller-Gärtner, H.-W.; Larisch, R. (Nuklearmedizin - NuclearMedicine, 2002)
Aim: The study presented here firstly compars the distribution of the binding potential of the serotonin-5HT2A receptor as measured in vivo with data of receptor density taken from literature. Secondly, the sensitivity of the method to detect gradual differences in receptor densities is evaluated. Methods: Positron emission tomography (PET) studies were carried out in 6 healthy volunteers using the selective serotonin-5HT2A ligand 18F-altanserin. The binding potential was quantified in 12 regions using Logan’s graphical method and the equilibrium method. These data were compared to the distribution of receptor density as taken from literature. Results: The binding data in vivo correlated to autoradiography data (post mortem) with r = 0.83 (Pearson regression coefficient; p <0.0001). A difference in the receptor density between two regions could be detected with p <0.05 when it amounted at least to 18%. Conclusion: This study demonstrates a good agreement between in vivo data obtained with 18F-altanserin and PET in healthy volunteers and the true autoradiographically determined distribution of 5HT2A receptors in human brains. The in vivo method seems to be sensitive enough to detect changes in receptor density of more than 18%.
Keywords: Serotonin receptor; 5-HT2A; PET; autoradiography